Emotional Intelligence as a Factor of Personal Life Fulfilment - Karpenko, Yevhen (Psychological Prospects Journal, 2017)
The article analyzes the phenomena of comprehension and interpretation, hermeneutic categories involved in the process of personal life fulfilment. Comprehension has been found to function at both the conscious and unconscious levels. It is an integral component of inter- and intrapersonal aspects of emotional intelligence and carries out an evaluation function in the process of life fulfilment. Comprehension facilitates acquisition of meaning at the situational, characterological and basic levels of identity and the assessment of its congruence with intra- and extra-psychic stimuli. In its turn, the organismic sense, which is an ability to be attentive and open to own physical and emotional manifestations indicating the right or wrong choice of life path on the basis of axiological peculiarities and dominant emotional attitudes, is the means of comprehension. Comprehension and interpretation are interdependent. It is due to interpretation that a person constructs his life path in the interpersonal interaction space. It is empowered by emotional competence, a component of emotional intelligence and an ability to self-regulate own emotions on the basis of pre-formed knowledge and skills, aimed at strengthening the effectiveness of social interaction, development of personal potential, life creation, etc. Therefore, it is worth explicating internal, external and integrative models of life. The first model mainly involves the organismic sense as a means of comprehension, the second – emotional competence which enables interpretation, and the most constructive third one provides for the harmonious combination of the first two models.
Keywords: comprehension, interpretation, meaning, organismic sense, emotional competence, emotional intelligence, life fulfilment.